PENGARUH HANDPHONE DAN TINGKAT KEDISIPLINAN BELAJAR TERHADAP PERILAKU MENYONTEK - Purwono, Herman (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Katolik Widya Mandala Madiun, 2014)
The media phone is no longer a thing layman, but it has become common used various circles without exception students. Based on the author's experience during was educated at the high school level, to get a satisfactory score many students that even opening the phone to cheating. Other factors that influence cheating behavior is the level of discipline learning. Based on the author's experience during was educated at the high school level, to get a satisfactory score many students the open mobile phones to cheat and which in turn get value almost perfect. In accordance with the background of the problem, the authors formulate the problem, namely: 1) what are the significant influence mobile phone usage on the incidence of cheating behavior? 2) what are the significant degree of influence disciplinary study on the incidence of behavior cheating? 3) what are the influence significant use of mobile phones and the level of discipline studying the behavior of cheating? This study aims to analyze the effect of mobile phones and the level of discipline studying the behavior of cheating. Population in this study were students of SMK PGRI Wonoasri, school year 2013/2014. Number of population is 163 students. The sampling technique Cluster sampling is used. Te Data were analyzed using regression techniques Multiple linear. The analysis showed that: 1) There is the influence of the use of HP (mobile) against cheating acceptable behavior. 2) There is influence the level of discipline of learning to cheating behavior acceptable. 3) There is the influence HP uses and levels of learning discipline, against cheating acceptable behavior. The use of mobile phones and the level of discipline learn to give a contribution of 61.4% against cheating behavior, while the rest 38.6% influenced by other variables not examined in this study.